Preparation method of composite photocatalytic material for activating persulfate

By growing NiFe-LDH in situ on CeO2 nanosheets to form a composite material with a core-shell structure, the problem of low performance of photocatalyst activated persulfate is solved, the degradation efficiency of tetracycline is significantly improved, and the stable circulation performance is maintained.

CN119425707APending Publication Date: 2025-02-14QINGHAI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371121.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing photocatalysts have low performance when activated persulfate (PMS), resulting in low efficiency in degradation of organic pollutants, especially in the treatment of antibiotic-containing wastewater.

Method used

NiFe-LDH was uniformly grown on CeO2 nanosheets in situ by hydrothermal method to form a core-shell structure NiFe-LDH/CeO2 composite material to improve the activation efficiency of PMS.

Benefits of technology

The composite material significantly improves the degradation efficiency of tetracycline under the PMS/Vis system, with a degradation efficiency of 98.8%, and has good stability during recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425707A_ABST
    Figure CN119425707A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite photocatalytic material for activating persulfate, and relates to the technical field of environmental protection, the composite photocatalytic material takes a CeO2 nanosheet as a core, layered double hydroxides grow in situ on the surface of the CeO2 nanosheet through a hydrothermal reaction to form a core-shell structure, and the metals are nickel and iron. CeO2 and a NiFe-LDH nano structure are ingeniously combined, so that absorption of visible light is increased, separation of photo-generated charges is promoted, persulfate can be activated to generate active free radicals, and then effective removal of antibiotic pollutants is achieved. Wherein the persulfate is potassium hydrogen persulfate, and the antibiotic pollutant is tetracycline hydrochloride. The method is simple to operate, and the prepared material is stable in performance and has certain application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of environmental protection technology and relates to a method for preparing a composite photocatalytic material for activating persulfate. Background Art

[0002] In recent years, organic pollution has replaced microbial pollution as the biggest hazard in water pollution, especially the pollution of medical antibiotics, which needs to be effectively controlled. The excessive use of antibiotics has caused great harm to the water environment. When the concentration of antibiotics in the water environment exceeds the safety threshold, it will inevitably endanger human health. Tetracycline is a highly effective broad-spectrum prescription antibiotic and one of the main antibiotics used as veterinary drugs or feed additives in human medicine and animal husbandry. However, tetracycline is difficult to eliminate in the natural environment. Therefore, it is crucial to develop an efficient and green treatment method to remove residual tetracycline in the environment.

[0003] Advanced oxidation processes (AOPs) have been shown to decompose refractory compounds into small molecular pollutants, and even completely degrade them into water and carbon dioxide by producing active oxidizing species. As a special type of AOPs, photocatalyst activated persulfate (PMS) technology is an ideal and efficient method for treating antibiotic-containing wastewater by generating highly active free radicals in situ. It is significantly superior to traditional wastewater treatment methods in terms of cost and practicality, and has great development prospects. However, how to improve the performance of photocatalysts remains a bottleneck restricting the pollutant degradation process.

[0004] In recent years, layered double hydroxides (LDHs), as a new type of semiconductor photocatalytic material, provide a new way to activate persulfate and are widely used in the degradation of organic pollutants due to their unique structural advantages. However, the original LDHs material has low reaction activity when used alone as a photocatalyst due to its low utilization of visible light and poor carrier separation efficiency. At the same time, researchers have found that by coupling with other semiconductor materials to form a heterostructure, the activation efficiency of the composite material for persulfate can be effectively improved, thereby improving the degradation efficiency of organic pollutants. Summary of the invention

[0005] In view of the above problems, the purpose of the present application is to provide a method for preparing a composite photocatalytic material for activating persulfate, by using a hydrothermal method to uniformly grow NiFe-LDH in situ on CeO 2 Core-shell structure NiFe-LDH / CeO on nanosheets 2 Nanocomposite materials effectively promote the activation of PMS.

[0006] The present application provides a method for preparing a LDH core-shell composite photocatalytic material for activating persulfate, which specifically comprises the following steps:

[0007] Step 1: Ce(NO 3 ) 2 6H 2 O and NH 4 HCO 3 respectively dissolved in deionized water to form a first solution and a second solution;

[0008] Step 2, quickly mixing the first solution and the second solution obtained in step 1, stirring under magnetic force to obtain a mixed third solution, and then aging the obtained mixed third solution in a water bath to form a precipitate;

[0009] Step 3: Filter, wash, dry and calcine the precipitate obtained in step 2 to obtain CeO 2 Nanosheets;

[0010] Step 4: The CeO obtained in step 3 2 The nanosheets were ultrasonically dispersed in deionized water and NiSO 4 6H 2 O, FeSO 4 7H 2 O、Na 3 C 6 H 5 O 7 ·2H 2 O and urea, stirred and dissolved, and after hydrothermal reaction, the core-shell structure of NiFe-LDH / CeO was obtained. 2 Composite photocatalytic materials.

[0011] Further, in step 1, Ce(NO 3 ) 2 6H 2 O and NH 4 HCO 3 The molar ratio is 1:3.

[0012] Furthermore, the stirring time in step 2 is 30 minutes.

[0013] Furthermore, the temperature of the water bath in step 2 is 30° C., and the aging time is 24 hours.

[0014] Furthermore, the drying condition in step three is vacuum drying at 60° C. for 2 h.

[0015] Furthermore, the calcination temperature in step three is 500° C., and the calcination time is 4 hours.

[0016] Further, the NiSO 4 6H 2 O and CeO 2 The molar ratio is 3 to 5:1.

[0017] Further, the NiSO 4 6H 2 O, FeSO 4 7H 2 O、Na 3 C 6 H 5 O 7 ·2H 2 The molar ratio of O and urea is 6:3:0.6:16.

[0018] Furthermore, the temperature of the hydrothermal reaction in step 4 is 180° C., and the time of the hydrothermal reaction is 12 h.

[0019] Furthermore, the composite photocatalytic material is obtained by in-situ growth of NiFe-LDH nanosheets uniformly wrapped in CeO 2 surface, forming a heterogeneous core-shell structure.

[0020] Furthermore, the core-shell composite photocatalytic material can effectively degrade tetracycline hydrochloride.

[0021] Furthermore, 0.1-0.4 g / L of the composite photocatalytic material is added to a tetracycline solution with a concentration of 5 mg / L-30 mg / L, and adsorbed with stirring for 40 min in dark conditions, and then 0.2-0.5 mM potassium persulfate (PMS) is added, and the solution is subjected to light irradiation reaction for 40 min under a 300 W xenon lamp.

[0022] The present application provides a method for preparing a composite photocatalytic material for activating persulfate, wherein NiFe-LDH is uniformly grown in situ on CeO by a hydrothermal method. 2 Core-shell structure NiFe-LDH / CeO on nanosheets 2 Nanocomposites have good interface contact between nanostructures, which not only effectively broadens the absorption range of visible light, but also helps the formation of heterogeneous structures, improves charge transfer, and effectively promotes the activation of PMS. The composite material shows satisfactory degradation efficiency for TC in the PMS / Vis system. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD pattern of the sample prepared for this application.

[0024] Figure 2 The SEM and TEM images of the samples prepared in this application, where a and b are CeO2 SEM and TEM images of a; c, d are SEM and TEM images of NiFe-LDH; e, f are SEM and TEM images of NFC-4.

[0025] Figure 3 Element mapping diagram of the NFC-4 sample prepared for this application.

[0026] Figure 4 The degradation efficiency of TC by the samples prepared in this application under different reaction systems, where a is the light-only condition, b is the PMS-only condition, c is the PMS / light condition, and d is the degradation reaction kinetic curve.

[0027] Figure 5 Effect of the NFC-4 sample prepared for this application on the degradation efficiency of TC under different experimental conditions, where a is the initial concentration of TC, b is the amount of catalyst added, and c is the PMS concentration.

[0028] Figure 6 The degradation performance of the NFC-4 sample prepared in this application after four cycles of use.

[0029] Figure 7 Degradation performance of the samples prepared for this application in the presence of different quenchers.

[0030] Figure 8 This is the electron spin resonance spectrum of the sample prepared in this application under the PMS / Vis system, where a is DMPO-SO 4 .- and DMPO-·OH, b is DMPO- · O 2 ˉ .

[0031] Fig. 9 NiFe-LDH / CeO prepared for this application 2 Schematic diagram of the composite material. DETAILED DESCRIPTION

[0032] In order to make the technical means, creative features, objectives and effects achieved by this application easy to understand, the following is a further description of this application in conjunction with specific embodiments and drawings, but the following embodiments are only preferred embodiments of this application, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of this application.

[0033] The present application provides a method for preparing a composite photocatalytic material for activating persulfate, comprising the following steps:

[0034] Step A: CeO 2Preparation of nanosheets;

[0035] Step B: Preparation of NiFe-LDH nanomaterials;

[0036] Step C: NiFe-LDH / CeO 2 -3 (NFC-3) core-shell composite photocatalytic material preparation;

[0037] Step D: NiFe-LDH / CeO 2 -4 (NFC-4) core-shell composite photocatalytic material preparation;

[0038] Step E: NiFe-LDH / CeO 2 -5 (NFC-5) core-shell composite photocatalytic material.

[0039] Specifically, combined Figure 1-Figure 9 As shown, each of the above steps is described by way of embodiments.

[0040] Example 1: CeO 2 Preparation of nanosheets

[0041] Preparation of CeO by low temperature hydrothermal method 2 Nanosheets, specifically comprising the following steps:

[0042] 2.78 g Ce(NO 3 ) 2 6H 2 O and 1.50 g NH 4 HCO 3 respectively dissolved in 100 mL of deionized water to form a first solution and a second solution, wherein the first solution and the second solution are both transparent solutions;

[0043] The first solution and the second solution were quickly mixed and stirred for 30 minutes to obtain a mixed third solution;

[0044] The mixed third solution was placed in a 30°C water bath and aged for 24 hours to form a precipitate;

[0045] The precipitate was then filtered, washed, and dried in an oven at 80°C overnight;

[0046] Finally, the obtained white precipitate was calcined in a muffle furnace at 500 °C for 4 h to obtain pure CeO 2 Nanosheets.

[0047] Example 2: Preparation of NiFe-LDH nanomaterials

[0048] The NiFe-LDH nanomaterials were prepared by a hydrothermal method, which specifically included the following steps: 394.2 mg NiSO4 6H 2 O, 208.5 mg FeSO 4 7H 2 O, 44.1 mg Na 3 C 6 H 5 O 7 ·2H 2 O and 240 mg of urea were added to 60 mL of deionized water to obtain a mixed fourth solution;

[0049] The fourth solution was stirred for 30 min and then transferred to a stainless steel reactor lined with polytetrafluoroethylene;

[0050] Hydrothermal reaction at 180℃ for 12h;

[0051] Filter, wash, precipitate and dry;

[0052] Finally, pure NiFe-LDH nanomaterials were obtained.

[0053] Example 3: NiFe-LDH / CeO 2 Preparation of NFC-3 core-shell composite photocatalytic materials

[0054] 86.0 mg of CeO obtained in Example 1 was added 2 The nanosheets were ultrasonically dispersed in 60 mL of deionized water and stirred for 20 min to obtain a fifth solution;

[0055] Add 394.2 mg NiSO to the fifth solution 4 6H 2 O, 208.5 mg FeSO 4 7H 2 O, 44.1mgNa 3 C 6 H 5 O 7 ·2H 2 O and 240 mg of urea, and continue stirring for 30 min to obtain a mixed fifth solution;

[0056] The fifth solution was added into a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180°C for 12h;

[0057] Filter, wash and dry the precipitate.

[0058] Example 4: NiFe-LDH / CeO 2 Preparation of NFC-4 core-shell composite photocatalytic materials

[0059] 64.5 mg of CeO obtained in Example 1 was added 2The nanosheets were ultrasonically dispersed in 60 mL of deionized water and stirred for 20 min to obtain a sixth solution;

[0060] Add 394.2 mg NiSO to the sixth solution 4 6H 2 O, 208.5 mg FeSO 4 7H 2 O, 44.1mgNa 3 C 6 H 5 O 7 2H2O and 240 mg urea, continue stirring for 30 min to obtain a mixed seventh solution;

[0061] The seventh solution was added into a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180°C for 12h;

[0062] Filter, wash and dry the precipitate.

[0063] Example 5: NiFe-LDH / CeO 2 Preparation of NFC-5 core-shell composite photocatalytic materials

[0064] 51.6 mg of CeO obtained in Example 1 was added 2 The nanosheets were ultrasonically dispersed in 60 mL of deionized water and stirred for 20 min to obtain an eighth solution;

[0065] Add 394.2 mg NiSO to the above solution. 4 6H 2 O, 208.5 mg FeSO 4 7H 2 O, 44.1mgNa 3 C 6 H 5 O 7 ·2H 2 O and 240 mg of urea, and continued stirring for 30 min to obtain a mixed ninth solution;

[0066] The ninth solution was added into a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180°C for 12h;

[0067] Filter, wash and dry the precipitate.

[0068] Figure 1 The XRD (X-ray Diffraction, referred to as XRD) spectra of the photocatalytic materials prepared in Examples 1 to 5. As can be seen from the figure, the original CeO 2The diffraction peaks of NiFe-LDH are located at 28.3°, 32.8°, 47.0°, and 56.4°, corresponding to the (111), (200), (220), and (311) crystal planes, respectively, which are consistent with the cubic fluorite structure. In the XRD spectrum of NiFe-LDH, the diffraction peaks of (003), (006), (012), and (110) crystal planes can be observed at 11.5°, 23.2°, 34.5°, and 60.2°, respectively. In addition, for NiFe-LDH / CeO 2 Composite material, XRD spectrum shows NiFe-LDH and CeO 2 The characteristic peaks of CeO 2 As the addition amount increases, the diffraction peak intensity of NiFe-LDH gradually increases, confirming that NiFe-LDH / CeO 2 Successful synthesis of composite materials.

[0069] Figure 2 The SEM (Scanning Electron Microscope, SEM) and TEM (Transmission Electron Microscope, TEM) images of the samples prepared in this application, where a and b are CeO 2 SEM and TEM images of a; c, d are SEM and TEM images of NiFe-LDH; e, f are SEM and TEM images of NFC-4. Figure 3 The element mapping diagram of the NFC-4 sample prepared in this application. The morphology of the photocatalytic materials of Example 1, Example 2 and Example 4 was analyzed, and the results are as follows: Figure 2 As shown. Original CeO 2 The pure NiFe-LDH sample shows a flower-like structure composed of ultra-thin two-dimensional layers. From the SEM and TEM images of the composite material NFC-4 sample, it can be seen that the NiFe-LDH nanosheets are uniformly grown in situ on the CeO 2 The surface of NiFe-LDH and CeO 2 There is an obvious interface contact between them, which is conducive to the transfer of photogenerated electrons and the activation of PMS, thus facilitating the further degradation of pollutants. Figure 3 As shown in the figure, the spatial composition and distribution of Ce, Ni and Fe in the NFC-4 composite material can be clearly distinguished from the EDX element mapping image of the NFC-4 sample, which further confirms the formation of the core-shell nanostructure and the NiFe-LDH / CeO2 Synthesis of composite materials.

[0070] Figure 4 The degradation efficiency of TC under different reaction systems of the samples prepared in this application, where a is the light-only condition, b is the PMS-only condition, c is the PMS / light condition, and d is the degradation reaction kinetic curve. The degradation performance curves of the photocatalytic materials of Examples 1-5 under different reaction systems for TC are shown in FIG. Figure 4 As shown. Figure 4 As shown in a, without adding PMS, CeO 2 and NiFe-LDH have lower photocatalytic degradation performance, although compared with single CeO 2 Compared with NiFe-LDH, NiFe-LDH / CeO 2 The photocatalytic activity of the composite material has been improved to a certain extent, but the highest degradation efficiency is still less than 40%, which indicates that a sufficient number of active free radicals cannot be generated in the photocatalyst / visible light system. Figure 4 b is the efficiency curve of catalyst activation of PMS to degrade TC under dark conditions. It can be seen that different catalysts have certain activation performance for PMS, and CeO 2 The activation efficiency of PMS is slightly higher than that of NiFe-LDH, which is consistent with the results reported in the literature. In the presence of catalyst, PMS and visible light, the removal efficiency of TC is effectively improved, indicating that the degradation process of TC is completed under the synergistic effect of the three. Figure 4 As shown in c, the degradation efficiency of TC by NFC-3, NFC-4 and NFC-5 samples reached 85.1%, 98.8% and 91.4%, respectively, which is much higher than that of CeO 2 (44.8%) and NiFe-LDH (28.5%). Figure 4 The reaction rate constants of the composites presented in d also illustrate this conclusion.

[0071] Figure 5 The effect of the NFC-4 sample prepared for this application on the degradation efficiency of TC under different experimental conditions, where a is the initial concentration of TC, b is the amount of catalyst added, and c is the concentration of PMS. The effect of the photocatalytic material of Example 4 on the degradation efficiency of TC under different experimental conditions (such as the initial concentration of TC, the amount of catalyst added, and the concentration of PMS) was investigated, and the results are as follows: Figure 5As shown. From the degradation efficiency of TC of different concentrations by NFC-4 composite material under PMS / Vis system, it can be seen that the reaction system can well complete the degradation of TC of different concentrations. After 40 minutes of reaction, the removal efficiency of 30mg / LTC solution can still reach 85.4%. At the same time, as the addition amount of NFC-4 catalyst increases from 0.1mg / L to 0.25mg / L, the number of reactive sites in the system will also increase, resulting in a significant improvement in the removal efficiency of TC. In addition, due to SO 4 ·- Active free radicals are generated after PMS activation and decomposition. The effect of PMS concentration on TC degradation was also investigated. Initially, with the increase of PMS concentration, a large number of PMS molecules were activated to produce more SO 4 ·- Free radicals are generated, which is beneficial to TC degradation. When the number of PMS molecules that can be activated in the system reaches saturation, the excess PMS molecules will react with the SO generated in the system. 4 ·- A reaction occurs, thereby consuming some of the active free radicals, causing the degradation efficiency to no longer continue to increase.

[0072] Figure 6 The degradation performance of the NFC-4 sample prepared in this application after four cycles of use. The recycling performance of the photocatalytic material of Example 4 was tested, and the results are as follows: Figure 6 Under the same experimental conditions, the degradation efficiency of TC in the four cycle experiments reached 98.8%, 97.2%, 95.5% and 94.7%, respectively, and the degradation efficiency was only reduced by 4.1%, indicating that the synthesized composite material is stable in the continuous photocatalytic reaction process.

[0073] Figure 7 The degradation performance of the samples prepared for this application in the presence of different quenchers. Figure 7 As shown in Figure 2, the performance curve of NFC-4 composite material in the presence of different capture agents to activate PMS and degrade TC under visible light. It can be seen that the addition of various capture agents leads to a decrease in the degradation efficiency of TC, indicating that SO 4 .- ,·OH,·O 2 - and h + Active species such as SO 4 .- ,·OH,·O 2 - and h +After the active species such as methanol, tert-butyl alcohol (TBA), benzoquinone (BQ) and ammonium oxalate (AO) were captured, the removal efficiency of TC decreased from 98.8% to 24.3%, 92.2%, 77.8% and 90.1%, respectively. This result shows that in the NFC-4 / PMS / Vis system, SO 4 .- It plays a leading role in the degradation of TC.

[0074] Figure 8 This is the electron spin resonance spectrum of the sample prepared in this application under the PMS / Vis system, where a is DMPO-SO 4 .- and DMPO-·OH, b is DMPO- · O 2 ˉ The presence of active free radicals in the reaction system was further confirmed by using the electron propagation resonance (EPR) technique. Figure 8 After 10 min of visible light irradiation, no active free radicals were found in the PMS / Vis system, while SO 4 .- ,·OH and ·O 2 - This further confirms the efficient activation of PMS by the NFC-4 composite under visible light irradiation.

[0075] Although the present application is described herein in conjunction with various embodiments, in the process of implementing the claimed application, those skilled in the art may understand and implement other changes to the disclosed embodiments by viewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "one" or "an" does not exclude multiple situations. A single processor or other unit may implement several functions listed in the claims. Certain measures are recorded in different dependent claims, but this does not mean that these measures cannot be combined to produce good results.

[0076] Although the present application has been described in conjunction with specific features and embodiments thereof, it is obvious that various modifications and combinations may be made thereto without departing from the spirit and scope of the present application. Accordingly, this specification and the drawings are merely exemplary illustrations of the present application as defined by the appended claims, and are deemed to have covered any and all modifications, variations, combinations or equivalents within the scope of the present application. Obviously, those skilled in the art may make various modifications and variations to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

[0077] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a composite photocatalytic material for activating persulfate, characterized in that: The method comprises the following steps: Step 1: dissolving Ce(NO3)2·6H2O and NH4HCO3 in deionized water to form a first solution and a second solution, respectively; Step 2: quickly mixing the first solution and the second solution obtained in step 1, and stirring under magnetic force to obtain a mixed third solution, and then aging the obtained mixed third solution in a water bath to form a precipitate; Step 3: filtering, washing, drying, and calcining the precipitate obtained in step 2 to obtain CeO2 nanosheets; Step 4: Ultrasonic disperse the CeO2 nanosheets obtained in step 3 in deionized water, add NiSO4·6H2O, FeSO4·7H2O, Na3C6H5O7·2H2O and urea, stir and dissolve, and after hydrothermal reaction, obtain a core-shell structured NiFe-LDH / CeO2 composite photocatalytic material.

2. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: In the step 1, the molar ratio of Ce(NO3)2·6H2O to NH4HCO3 is 1:

3.

3. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: In the step 2, the stirring time is 30 minutes, the temperature of the water bath is 30° C., and the aging time is 24 hours.

4. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: In the step three, the drying condition is vacuum drying at 60° C. for 2 h; the calcination temperature is 500° C., and the calcination time is 4 h.

5. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: In the step 4, the molar ratio of the NiSO4·6H2O to the CeO2 is 3-5:1; the molar ratio of the NiSO4·6H2O, the FeSO4·7H2O, the Na3C6H5O7·2H2O and the urea is 6:3:0.6:

16.

6. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: In the step 4, the temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 12 hours.

7. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: The composite photocatalytic material is prepared by uniformly wrapping NiFe-LDH nanosheets on the surface of CeO2 through an in-situ growth method to form a heterogeneous nucleus-shell structure; the composite photocatalytic material can effectively degrade tetracycline hydrochloride.

8. The method for preparing a composite photocatalytic material for activating persulfate according to claim 1, characterized in that: 0.1-0.4 g / L of the composite photocatalytic material was added to a tetracycline solution with a concentration of 5 mg / L-30 mg / L, and adsorbed with stirring for 40 min in the dark. Then 0.2-0.5 mM potassium persulfate (PMS) was added, and the reaction was carried out under a 300 W xenon lamp for 40 min.